Assembly of branched ubiquitin oligomers by click chemistry. Issue 87 (15th October 2019) - Zhao, Xiaohui; Scheffner, Martin; Marx, Andreas
Abstract : Ubiquitin monomers functionalized with an azide or multiple alkynes were utilized for the assembly of branched ubiquitin oligomers that exhibit stability in eukaryotic cell lysates. Abstract : Ubiquitin monomers functionalized with an azide or multiple alkynes were utilized for the assembly of branched ubiquitin oligomers (K6/K11, K11/K48, K11/K63, K6/K11/K48) by click chemistry. The oligomers resist deubiquitylase-catalysed hydrolysis and exhibit stability in eukaryotic cell lysates.